Improving students’ ability in learning mathematics by using the science, technology, engineering, and mathematics (STEM) approach - Ilyas, Muhammad; Meiyani, Eliza; Ma’rufi, Ma’rufi; Kaewhanam, Phimlikid (Frontiers in Education, 2022)
The science, technology, engineering, and mathematics (STEM) approach is a leading and important learning approach to analyze thinking ability and learning motivation. Accordingly, this study attempts to elaborate a STEM approach to analyze the critical thinking ability and motivation of high school students in Indonesia, especially in Palopo City, South Sulawesi, Indonesia. The current research applied pre-experimental treatment on research objects involving a group of experimental classes. Pre-experimental was used in testing the STEM approach in an experimental class with a one-group pretest-posttest design with 176 students divided into five classes. The results show: 1) improvement in students' critical thinking ability indicated by an average pre-test score of 13.90 and post-test score of 70.67; 2) an increase in student learning motivation shown by an average of 71.57 to 80.83. The analysis results show an increase in students' critical thinking ability and learning motivation after applying the STEM approach. Conclusively, STEM functions as one of the practical learning methods for improving students' critical thinking skills and learning motivation.